Efficiency for Whom?: The Effect of Efficiency on Indonesian Islamic Commercial Bank’s Deposit Return - Rahmiyanti, Firdha (Falah: Jurnal Ekonomi Syariah, 2018)
The main purpose of this paper is to examine the compliance of efficiency and deposit return in Indonesian Islamic commercial bank. The Sample includes an annual panel from 2005 to 2014. The data collected during the period 2005-2014 based on the annual report of Islamic banking that financial information is available. This research exclusively focus on commercial Islamic banking. To account for profit persistence, we apply a GMM technique to a panel secondary data which obtained from audited financial reports of 12 Indonesian Islamic Commercial banks in existence as at the end of 2015. The result of this study is that an efficiency on Islamic Commercial Bank’s Deposit has a positive effect on deposit return.